ANALISIS KIMIA BEBERAPA KAYU KURANG DIKENAL DARI NUSA TENGGARA BARAT - Gustan Pari; Djeni Hendra (Jurnal Penelitian Hasil Hutan, 1991)
This paper  deals with chemical analysis of ten lesser known  wood species  from Nusa Tenggara  Bara   The analyisi  comprises  of determination of  holocellulose,  cellulose, lignin, pentosan, silica, ash,   moisture contents and solubility in cold water,  hot  water,  sodium  hydroxide  and  alcohol  benzene content.The result shows that holiocellulose  content  ranges  from 53,5 -  68. 8 percent, cellulose from 43. 0 -   62. 3 percent.  Low cellulose content  was formed in Duabanga  molucana.  Lignin content varie from 20.2- 24.7 percent, pentomn con-  tent from  8.0   15.4 percent. Lignin and pentosan  content of all wood species  examined  were in moderate  and  low.   Moisture content  ranged  from  10.7 -  25.3  percent,   ash content from  0.2 -   2.1 percent, silica from Q. 1-1.0 percent.The solubility  in cold water ranged from  3.0  -   10.2 percent,  in hot  water  from 5.4 – 14.1 percent, in one  percent  of sodium hydroxide  solution from 9. 7 -   35.0 percent  and in alcohol benzene (1:2) from 1.5-7.0 percent. The   extractive contents of  Elaeocarpus sphserlcus,Eugenia lineata  Palaquium   javaneae  and Duabanga molucana    wood species are  having low component  cless.flcus microcarpus and Trema  orientalia   wood  sapecia  had moderate extractwe component  class  Ailanthus  malabarica,  Aathoaspelalus   cadamba  and   eugenia   polyantha   wood species  included in high extractiue component. class Based on chemical analysis  especially  the cellulose and pentosan  content  of  the  10 lasser known wood species from Nusa  Tenggara Barat are suitable as  raw material for  pulp and peper industry.